FEATURES OF THE SYNDROMES OF OSTEOPOROSIS AND SARCOPENIA IN RHEUMATOID ARTHRITIS WITH MUSCLE WEAKNESS - Akhmedov Ibrat; Islamova Kamola; Abdushukurova Komila; Toshnazarova Nodira (Journals Park Publishing, 2023)
Objective. The aim of the study was to evaluate the syndromes of sarcopenia (SP) and osteoporosis (OP) in RA patients with muscle weakness.
Keywords: rheumatoid arthritis, sarcopenia, SARC-F, osteoporosis.